Effects of limestone and gypsum application to a Malaysian ultisol on soil solution composition and yields of maize and groundnut - Shamshuddin, J.; I., Che Fauziah; Sharifuddin, H.A.H. (Kluwer Academic, 1991)
A field experiment was conducted on an Ultisol in Malaysia to assess changes in soil solution composition and their effects on maize and groundnut yields, resulting from limestone and gypsum application. The results showed that soil solution Ca in the lime treatment remained mainly in the zone of incorporation, but in the gypsum treatment some Ca moved into 15-30 cm zone. Al3+ and AlSO4+ were dominant Al species in the soil solution of nil treatment. Liming decreased Al3+ and AlSO4+, but increased hydroxy-Al monomer activities. However, gypsum application resulted in an increase of AlSO4+ activity and in a decrease of Al3+ activity. Relative maize and groundnut yields were negatively correlated with Al3+, Al(OH)2+ and Alsum activities. Likewise, relative yields were negatively correlated with Al concentration and the Al concentration ratio and positively correlated with soil solution Mg concentration and Ca/Al ratio.